Continuities of influence: A critical analysis of subject English in the New South Wales' secondary school curriculum of 1911. Issue 1 (5th June 2017) - Manuel, Jacqueline; Carter, Don
Abstract : Purpose: This paper provides a critical interpretative analysis of the first secondary English syllabus for schools in New South Wales (NSW), Australia, contained within the Courses for Study for High Schools (New South Wales Department of Public Instruction, 1911). The purpose of the paper is to examine the "continuities that link English curriculum discourses and practices with previous discourses and practices" in the rhetorical curriculum. The analysis identifies those aspects of the 1911 English syllabus that have since become normative and challenges the appropriateness of certain enduring orthodoxies in a twenty-first century context. Design/methodology/approach: Focussing on a landmark historical curriculum document from 1911, this paper draws on methods of historical comparative and documentary analysis. It sits within the tradition of historical curriculum research that critiques curriculum documents as a primary source for understanding continuities of discourses and practices. A social constructionist approach informs the analysis. Findings: The conceptualisation of subject English evident in the structure, content and emphases of the 1911 English syllabus encodes a range of "discourses and practices" that have in some form endured or been "reconstituted and remade" (Cormack, 2008, p. 275) over the course of a century. The analysis draws attention to those aspects of the subject that have remained unproblematised and taken-for-granted, and the implications of this for universal student participation and attainment. Originality/value: This paper reorients critical attention to a significant historical curriculum document that has not, to date, been explored against the backdrop twenty-first century senior secondary English curriculum. In doing so, it presents extended insights into a range of now normative structures, beliefs, ideas, assumptions and practices and questions the potential impact of these on student learning, access and achievement in senior secondary English in NSW in the twenty-first century.